Responding to Breast Cancer in Ghana: The Role of State and Non State Actors - Daffour, P.A. (University of Ghana, 2015)
This is a qualitative study of the role of state and non-state actors in responding to breast cancer in Ghana. In depth interviews were conducted with eight purposively sampled actors comprising five and three actors from state and non-state actors respectively.The objectives of the study is to investigate the perspectives of State and Non-State actors on the causes and risk factors of breast cancer in Ghana, identify the roles they play in responding to the issue of breast cancer in Ghana, assess the policy interventions towards aiding individuals with Breast Cancer and their challenges. Findings from the study reveal biological and lifestyle practices that put women at risk of having breast cancer, state and non-state actors played very important roles in addressing breast cancer issues in Ghana, The study further discovered that both state and non- sate actors contributed to the development of interventions that were directly or indirectly adopted into health policies. Financial constraints and socio-cultural beliefs and practices were identified to be the most dominant challenges to the impact of both state and non-state actors in their efforts in addressing health issues relating to breast cancer health. The study identified collaborative efforts between both set of actors in public health initiatives with very significant contributions from the media. The study provides evidence of the need to put in place policies towards addressing social, technological and structural challenges faced by these actors.The study found the major roles played by the state and non-state actors, it included awareness creation, late detection, NGOs playing a critical role in addressing issues that were overlooked or ignored by government, resource challenges, perceptions, beliefs and cultural practices; ignorance and stigmatization, financial constraints, lack of professionals, public misconceptions about breast cancer and lack of scientific and epidemiologic information. The study recommends opportunities to change the negative perceptions of the public concerning breast cancer via awareness creation, and capacity building was recommended. In sum the study shows that both state and non-state actors among other things play a key role in the country‟s quest to address breast cancer.
Thesis (MPhil) - University of Ghana, 2015